2020
DOI: 10.37268/mjphm/vol.20/no.special1/art.701
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of Breastfeeding Chair for Nursery Room

Abstract: Breastfeeding chair is one of the essential facilities in the airport. This study designs the breastfeeding chair for the nursery room in Minangkabau International Airport. Quality Function Deployment (QFD) was used to investigate the customer requirements by distributing questionnaires to 100 mothers in Padang West Sumatra. Anthropometry data was also measured form those respondents. The study resulted in a design of ergonomic breastfeeding chair which was used features obtained from the voice of the customer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Using the resulting RULA score, it can be decided whether the design is suitable for the user and satisfies the health and safety considerations. The RULA analysis is a useful tool for estimating the MSDs that humans experience when engaging in activities such as everyday chores, sports, sitting positions, and other situations [ 35 ]. This tool gives a score out of 7 (the highest score of risk), so a procedure should be taken to eliminate that score to be acceptable and reduce the risk factor of such posture.…”
Section: Methodsmentioning
confidence: 99%
“…Using the resulting RULA score, it can be decided whether the design is suitable for the user and satisfies the health and safety considerations. The RULA analysis is a useful tool for estimating the MSDs that humans experience when engaging in activities such as everyday chores, sports, sitting positions, and other situations [ 35 ]. This tool gives a score out of 7 (the highest score of risk), so a procedure should be taken to eliminate that score to be acceptable and reduce the risk factor of such posture.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, a survey of 100 mothers conducted by Prima et al revealed significant deficiencies in the design and comfort of the long couch-type breastfeeding chairs currently in use. The shortcomings include inadequate protection of the mother's privacy and insufficient consideration of supporting proper breastfeeding positions [ 6 ]. The existing problems with breastfeeding chairs are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%